Cartographies in Morro da Conceição: opening breaches in the body of the city - Torralba (Universidade Federal Fluminense ‒ UFF, Niterói/RJ, Brazil), Ruth (Revista Brasileira de Estudos da Presença, 2022)
The article is constituted through the drift lines of a dance research group in Morro da Conceição, located in the port area of Rio de Janeiro. The drift and the affective occupation in-with the space are affirmed as gestures-fissure in the space-time of the city. It is proposed a research in dance that weaves the edge with other knowledge and practices, in the transit zones of the body with the world, and that affectively occupies some spaces of the city, creating new body-city graphs.